TUTLÍǴÍWDÍ KORREKSIYALAWDA ARNAWLÍ USÍLLAR HÁM LOGOPEDIYALÍQ OYÍNLAR - Tajimuratov, A.J. (SCIENCE and SOCIETY, 2025)
The article presents special methods used in the correction of stuttering speech deficiency. The use of games in organizing activities with children gives effective results. With this in mind, logopedic games for stuttering correction are given as examples.